Agronomy to promote resilience for indigenous students and farmers in Fiji : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Horticulture Science at Massey University, Palmerston North, New Zealand - Savou, Joeli (Massey University, 2022)
"Nai takele ni kai viti na vuli – Ratu Sukua." Agriculture is acknowledged as one of the significant contributors to the Fijian economy (United Nations Pacific, 2021). The United Nations and the Secretariat of the Pacific Community have identified Fiji as a country with a vulnerable agriculture sector and high food security risks. This conclusion is owed to Fiji’s seasonal cyclones, inadequate extension programmes, lack of technical knowledge, and primitive farmer mindset (Asian Development Bank, 2011). Research suggests that indigenous Fijian people learn primarily through observation and practical application. Similarly, the transfer of knowledge is through stories, songs and dances, making them practical people. A change in the pedagogical approach in agricultural universities by including field trials and linking them with the theoretical experience will promote learning for our indigenous students. Moreover, there is space to explore teaching approaches that may be effective in training indigenous students. Opening training pathways that lead to a better understanding of developing critical thinking for indigenous students is imperative. Farm trials (applied in the appropriate context) can enhance understanding and improve outcomes to bridge the gap between theory, indigeneity, and practice in agronomy. These attributes help address current agricultural problems in Fiji, such as climate change and food security, which farmers can adopt to develop adaptive, resilient and robust approaches to improve production. The results generated through this paper reflected a positive outcome in terms of pedagogical approaches in tertiary level in Fiji. The incorporation of field trials in practical activities with the guide of assessments is proven to develop awareness and critical thinking in indigenous Fijian students. The formulated templates are a key component in undertaking field trials as they can be utilised to adapt to any crop.
Keywords: indigenous pedagogy; agronomy; field trials; climate change; food security; sustainability; resilience; 300299 Agriculture, land and farm management not elsewhere classified